Prevalence of stress and its associated factors among university staff - Mukosolu, Okonkwo; Ibrahim, Faisal; Gyanchand Rampal, Lekhraj Rampal; Ibrahim, Normala (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
Introduction: Stress in the work place is a global major risk factor to worker’s health, which triggers the workers to be poorly motivated and less productive. Objectives: The objective of the study was to determine the prevalence of job stress and its associated factors among Universiti Putra Malaysia staff.